High glucose environment induces M1 macrophage polarization that impairs keratinocyte migration via TNF-α: An important mechanism to delay the diabetic wound healing. Issue 3 (December 2019) - Huang, Shu-Mei; Wu, Ching-Shuang; Chiu, Min-Hsi; Wu, Chin-Han; Chang, Yu-Tang; Chen, Gwo-Shing; Lan, Cheng-Che E.
Highlights: Skin wound healing is associated with macrophage infiltration. Skin wounds in diabetic rats are associated with M1 type macrophage predominance with high levels of tumor necrosis factor alpha expression. in vitro studies demonstrate high glucose environment favors M1 type macrophage polarization that produces significant amount of TNF-α that is detrimental to keratinocyte migration. Neutralization of TNF-α improves wound healing in diabetic rats and may be a therapeutic option to promote wound healing in diabetics. Abstract: Background: Macrophages play important roles during wound healing, and delayed healing in diabetics is associated with sustained inflammation. M1 type macrophage is recognized to secrete excessive amount of tumor necrosis factor-alpha (TNF-α) as compared to its M2 counterpart. Objectives: We hypothesized that macrophage polarization is different between diabetic and normal rats during skin wounding and has direct impact on keratinocyte function in the context of re-epithelialization. Methods: Skin wounds were created in diabetic and control rats. The phenotypes of infiltrating macrophages, the levels of TNF-α, and the rate of wound closure were determined. Using cell model, the effects of M1 type macrophage on keratinocyte migration were evaluated, and the potential regulatory pathways were determined. Results: The percentage of M1 macrophages and the levels of TNF-α expression were significantly higher in the perilesional area of diabetic rats as compared to control. The condition media (CM) from M1 type macrophage upregulated tissue inhibitor metalloproteinases (TIMP)-1 expression in keratinocytes and significantly reduced keratinocyte migratory capacity. Addition of neutralizing TNF-α antibody to the CM or gene-silencing of TIMP1 in keratinocytes restored the keratinocyte migratory capacity. Treating wounds of diabetic rats with TNF-α antagonist improved the wound healing process. Conclusions: In summary, high glucose wound environment harbored more M1 macrophages infiltration, an event that created excess TNF-α micro-environment. TNF-α upregulated TIMP1 expression in keratinocytes and resulted in impaired keratinocyte migration. Taken together, these events contributed to impaired wound healing during diabetic condition, and targeting TNF-α is a potential therapeutic option to improve diabetic wound healing.